Konsep Diri terhadap Kepercayaan Diri Peserta Didik di Sekolah Menengah - Raihan, Muhammad; Alfita, Laili (Mahesa Research Center, 2025)
This study aims to examine the influence of self-concept on the self-confidence of secondary school students through a narrative literature review. Self-confidence is a crucial aspect of adolescents’ psychological development, and it can be shaped by how individuals perceive and evaluate themselves (self-concept). This research employed a literature review method by analyzing 16 national scientific articles published between 2015 and 2025. The findings reveal that a positive self-concept significantly contributes to enhancing students' self-confidence in both academic and social aspects. Several external factors, such as family support, school environment, and guidance counseling, were found to strengthen the development of a healthy self-concept. This review contributes to the synthesis of previous findings, providing a comprehensive understanding of the importance of self-concept reinforcement in education. The conclusion emphasizes that strengthening self-concept through a holistic approach can be an effective strategy to improve self-confidence among secondary school students